TREM2: Keeping Pace With Immune Checkpoint Inhibitors in Cancer Immunotherapy - Qiu, Hui; Shao, Zhiying; Wen, Xin; Jiang, Jinghua; Ma, Qinggong; Wang, Yan; Huang, Long; Ding, Xin; Zhang, Longzhen (Frontiers in Immunology, 2021)
To date, immune checkpoint inhibitors have been successively approved and widely used in clinical cancer treatments, however, the overall response rates are very low and almost all cancer patients eventually progressed to drug resistance, this was mainly due to the intricate tumor microenvironment and immune escape mechanisms of cancer cells. One of the main key mechanisms leading to the evasion of immune attack was the presence of the immunosuppressive microenvironment within tumors. Recently, several studies illustrated that triggering receptor expressed on myeloid cells-2 (TREM2), a transmembrane receptor of the immunoglobulin superfamily, was a crucial pathology-induced immune signaling hub, and it played a vital negative role in antitumor immunity, such as inhibiting the proliferation of T cells. Here, we reviewed the recent advances in the study of TREM2, especially focused on its regulation of tumor-related immune signaling pathways and its role as a novel target in cancer immunotherapy.